Electronic Delocalization in the Radical Cations of Porphyrin Oligomer Molecular Wires - Peeks, Martin D. (J Am Chem Soc, 2017)
[Image: see text] The radical cations of a family of π-conjugated porphyrin arrays have been investigated: linear chains of N = 1–6 porphyrins, a 6-porphyrin nanoring and a 12-porphyrin nanotube. The radical cations were generated in solution by chemical and electrochemical oxidation, and probed by vis–NIR–IR and EPR spectroscopies. The cations exhibit strong NIR bands at ∼1000 nm and 2000–5000 nm, which shift to longer wavelength with increasing oligomer length. Analysis of the NIR and IR spectra indicates that the polaron is delocalized over 2–3 porphyrin units in the linear oligomers. Some of the IR vibrational bands are strongly intensified on oxidation, and Fano-type antiresonances are observed when activated vibrations overlap with electronic transitions. The solution-phase EPR spectra of the radical cations have Gaussian lineshapes with linewidths proportional to N(–0.5), demonstrating that at room temperature the spin hops rapidly over the whole chain on the time scale of the hyperfine coupling (ca. 100 ns). Direct measurement of the hyperfine couplings through electron–nuclear double resonance (ENDOR) in frozen solution (80 K) indicates distribution of the spin over 2–3 porphyrin units for all the oligomers, except the 12-porphyrin nanotube, in which the spin is spread over about 4–6 porphyrins. These experimental studies of linear and cyclic cations give a consistent picture, which is supported by DFT calculations and multiparabolic modeling with a reorganization energy of 1400–2000 cm(–1) and coupling of 2000 cm(–1) for charge transfer between neighboring sites, placing the system in the Robin–Day class III.